Reexamining the Influence of Conditional Cash Transfers on Migration from a Gendered Lens: Comment - Oded Stark (Institute of Labor Economics (IZA), 2021)
In a recent article, "Reexamining the influence of conditional cash transfers on migration from a gendered lens," Hughes (2019) claimed that conditional cash transfers, CCT, limit the likelihood of migration by women, compensating them for giving up an attractive migration option. I question the analysis that lies behind this claim. I argue that in seeking to understand the likelihood of women migrating if they participate in a CCT program, issues of selectivity, endogeneity, and optimization cannot be set aside. In particular, it is not that receiving CCT curtails a migration option; it is that not contemplating migration encourages women to accept CCT. And if a household perspective is brought to bear, then a household's free choices weaken the appeal of migration to women. This reduction in appeal does not arise from an exogenously imposed curb but rather from endogenously determined preferences.
Keywords: B54; D13; G51; J16; J61; O15; R23; 330; women's migration; conditional cash transfers; selectivity and endogeneity; revision of the comparative advantage of household members; household's optimization